EVALUASI DESAIN LANSKAP TERHADAP PERILAKU MANUSIA DI KAWASAN WISATA PANTAI PULAU DATOK KABUPATEN KAYONG UTARA - Hadriyono, Hadriyono; Setyabudi, Irawan; Nailufar, Balqis (Universitas Tribhuwana Tunggadewi, 2019)
Pulau Datok Beach is one of the natural tourist attractions that has an attraction and has a very supportive tourism potential, is located across the province between North Kayong Regency and Ketapang Regency. The increasing number of visitors to the coast of Pulau Datok also has a positive impact on the economy of the local population and also leaves a negative impact on the beach, namely the behavior of visitors who do not dispose of garbage in place, vandalism and immoral acts that cause the quality of the islands coast to come. This study aims to determine the suitability of the carrying capacity of tourist areas with visitor behavior patterns whether it is in accordance with the carrying capacity of the tourist area standard with the appropriate identification, analysis, evaluation and design recommendations. This research method uses qualitative descriptive. The sampling technique was done by purposive sampling which is population sampling based on the criteria of gender and age, the sample obtained in the study location was divided into three samples, namely parents with 6 samples of 11 adolescents and children 5 samples. The results of this study for the carrying capacity of the island of Pulau Datok beach area still exist in some points that do not meet the standards that exist in the standard of carrying capacity of tourist areas so there should be a design recommendation that should be. Pantai pulau datok merupakan salah satu tempat wisata alam yang memiliki daya tarik dan memiliki potensi wisata yang sangat mendukung, Terletak dijalur lintas provinsi antara Kabupaten Kayong Utara dan Kabupaten Ketapang. Semakin tingginya jumlah pengunjung terhadap pantai pulau datok juga berdampak positif bagi perekonomian penduduk setempat dan juga menyisakan dampak negatif terhadap pantai yakni perilaku pengunjung yang tidak membuang sampah pada tempatnya, vandalisme dan tindakan asusila yang menyebabkan turunya kualitas pantai pulau datok. Penelitian ini bertujuan untuk mengetahui kesesuaian daya dukung kawasan wisata dengan pola perilaku pengunjung apakah sudah sesuai dengan daya dukung standar kawasan wisata dengan tahap identifikasi, analisis, evaluasi serta rekomendasi desain yang sesuai. Metode penelitian ini menggunakan deskriptif kualitatif . Teknik pengambilan sample dilakukan dengan purposive sampling yaitu pengambilan sample populasi berdasarkan kriteria gender dan usia, sample yang didapat dilokasi penelitian dibagi menjadi tiga sample yaitu orang tua dengan 6 sample remaja 11 sample dan anak-anak 5 sample. Hasil dari penelitian ini untuk daya dukung kawasan wisata pantai pulau datok masih ada di beberapa titik yang belum memenuhi standar yang ada pada standar daya dukung kawasan wisata sehingga harus adanya rekomendasi desain yang seharusnya.